Anti-icing mechanism of combined active ethanol spraying and passive surface wettability. (5th February 2023) - Li, Nan; Jiang, Jing; Yang, M.Y.; Wang, Hao; Ma, Yuan; Li, Zhe; Tang, G.H.
Graphical abstract: Highlights: The combined active and passive anti-icing performance is experimentally investigated. The hydrophilic surface presents freezing delay after spraying ethanol. The coupled mechanism of hydrophilic surface and solute is explored by molecular dynamics simulation. The solute on HPI surface inhibits formation of hexagonal network of ice-like molecules on substrate. Abstract: The combined active and passive anti-icing is widely concerned due to its high-efficiency in anti-icing applications. However, the microscopic mechanism of a complete active and passive anti-icing process is not yet clear. In this work, the freezing experiments of ethanol spraying on hydrophilic and superhydrophobic functional surfaces were carried out. The results of combined active and passive anti-icing experiments indicate that the active–passive technology can improve the ice inhibition performance, especially for the hydrophilic surface. Based on molecular dynamics simulations, the microscopic mechanisms of solution freezing on hydrophilic and superhydrophobic surfaces were revealed. Due to the adsorption of additive molecules on ice molecules and the interaction between additive molecules and the surface, the energy barrier of heterogeneous nucleation increases and the freezing temperature decreases. Therefore, the hydrophilic surface that was generally considered to be weak in ice inhibition shows an unexpected strong ice inhibition performance in the combined active and passive anti-icing process. The present work is helpful for developing combined active and passive anti-icing technology in practical engineering.